Genome-wide identification, transcriptome dynamics, and expression regulation of the key lignin biosynthesis gene families PAL and CAD in black walnut shell - Huijuan Zhou; Hengzhao Liu; Jiayu Ma; Ming Yue; Yaling Wang; Peng Zhao; Zhikun Chen (BMC Plant Biology)
Abstract Background Walnut (Juglans), cultivated globally for their nuts and timber, holds significant economic and ecological value. The eastern black walnut (EBW, J. nigra). a diploid species, an important woody species. Key enzymes in the plant lignin biosynthesis pathway include Phenylalanine ammonia-lyase (PAL) and Cinnamyl alcohol dehydrogenase (CAD). Although the gene families of PAL and CAD have been extensively characterized in various plants, comprehensive genomic resources and expression profiles specific to the EBW remain limited. Results Based on RNA sequencing of shells and kernels from black walnut (Juglans nigra) among three development stages, S1 (80 days after flowering, DAF), S2 (111 DAF), and S3(140 DAF) in black walnut shells and kernels, we found the genes related to lignin biosynthesis. genes such as JnPAL, JnC4H, Jn4CL1, Jn4CL2, JnHCT, JnCOMT, JnCAD2, and JnCAD-like exhibited significant differential expression across all three developmental stages. Both PAL and CAD genes were expressed significantly in walnut shells compared to kernels across three developmental stages. We conducted a genome-wide identification and discovered 7 PAL and 3 CAD proteins in J. nigra and 5 PAL and 3 CAD proteins in J. microcarpa genome, respectively. Transcriptome DEGs (differential expressed genes) analysis and identified three candidates PAL (JnPAL1, JnPAL2, and JnPAL6) and 2 CAD genes (JnCAD2 and JnCAD3) were upregulated during the development of walnut kernels and shells. In addition, it was higher expressed of these PAL and CAD genes in the shell than kernel. Conclusions We conducted a comprehensive involving genome-wide identification, transcriptome dynamics, and expression regulation of the key lignin biosynthesis gene families PAL and CAD across three development stages of shells. This study not only constitutes a valuable resource for elucidating the role of PAL and CAD genes in determining shell thickness in black walnut but also holds significant potential for informing gene-assisted breeding strategies in walnut cultivation.